Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/bf02782194
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated breast cancer: a case— control study in a young population with a high-fertility rate

Abstract: Pregnancy-associated breast cancer (PABC) is not a rare event. The association frequently imposes a management challenge. We intended to review the clinical features, therapy, and outcome of patients with PABC seen at a single institution over a five-year period and to compare those with that seen in a matched control group. Data of all patients with PABC diagnosed during pregnancy were retrospectively reviewed (Group I). For each patient in Group I, three matched controls with breast cancer without pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 19 publications
1
33
2
4
Order By: Relevance
“…Focusing on matched case-case studies, it is worth mentioning that our study is not in accordance with the study by Ibrahim et al [23] who pointed to a lack of survival difference between patients with PABC and their matched controls. Moreover, the majority of the large population-based studies have not found inferior survival for patients with PABC [10,11,12,13].…”
Section: Discussioncontrasting
confidence: 55%
“…Focusing on matched case-case studies, it is worth mentioning that our study is not in accordance with the study by Ibrahim et al [23] who pointed to a lack of survival difference between patients with PABC and their matched controls. Moreover, the majority of the large population-based studies have not found inferior survival for patients with PABC [10,11,12,13].…”
Section: Discussioncontrasting
confidence: 55%
“…Hence, following published methodology, 6,8,11 the PABC patients were matched with corresponding controls based on the institution of registration, year of registration and patient's age (± two years). The year of registration was used as the criterion for the purpose of obtaining uniformity regarding the type of diagnostic tests, classification systems and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis (using the Cox regression method) revealed that tumor size (≤ 3.0 cm versus > 3.0 cm), axillary lymph node involvement (0 versus 1-3 versus ≥ 4) and age (≤ 33 years versus > 33 years) each exerted an independent and significant influence on overall survival and on the emergence of metastasis. In contrast, Ibrahim et al 11 investigated 72 PABC patients together with their matching controls (216 non-pregnant women in the same condition), who were selected according to disease stage, year of diagnosis and age. Only disease stage was identified as significant with regard to overall survival according to the Cox model.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have noted that IBC is associated with pregnancy and/or lactation [27,37,53,55,68,75,90], whereas other series suggest that IBC is no more common for pregnancy-related tumors than for other breast cancer types [52,66,82]. In their classic description of IBC in 1924 [56], Lee and Tannenbaum did not find a single IBC case during pregnancy.…”
Section: Reproductive Factorsmentioning
confidence: 99%